Outcomes of delayed chest closure after congenital heart surgery in neonates - Meletios Kanakis; George Samanidis; Kyriaki Kolovou; Sotirios Katsaridis; Athina Maria Sait; Georgios Kourelis; Nicholas Giannopoulos; Dimitrios Bobos (PAGEPress Publications, 2024)
We present the outcomes of delayed chest closure in neonates who underwent congenital heart surgery under cardiopulmonary bypass. Eighty-one consecutive neonatal patients (age ≤ 28 days) with congenital heart diseases who underwent heart operations and after surgery, chest remained open in the intensive care unit until DCC. Correction of transposition of the great arteries pathology was the most common surgical procedure (48.1% of patients). Median sternal closure time from surgery was 3 (2-4) days. Median age of neonates was 9 (5-12) days. In addition, in 4 cases (4.9%) there was secretion from the surgical site after DCC and after taking cultures, in 2 (2.4%) of the cases a pathogen was identified. Multivariable linear regression analysis (adjusted to gender and CPB) showed that only the age-predicted the sternum closure time (β=-0.09, 95%CI: - 0.16 to -0.02, p=0.02). In-hospital mortality was 6 (7.4%) patients. Although the DCC in neonates who underwent CHD surgical correction was related to a high mortality rate, only the age of neonates predicted the sternum closure time in the ICU.